FUN ARABIC TEACHING WITH SONG MEDIA FOR PRIMARY SCHOOLS/PENGAJARAN BAHASA ARAB MENYENANGKAN DENGAN MEDIA LAGU UNTUK MADRASAH IBTIDAIYAH - Nuril Mufidah (STAI Ma'had Aly Al-Hikam Malang, 2019)
Primary students, especially the basic class, have many difficulties learning Arabic because they are not used in daily communication, and there are differences in Arabic alphabets. There needs to be learning alternatives that are appropriate for the child's age and bring Arabic closer. Arabic is a close foreign language for students of Muslim faith; because they used to recite daily Arabic prayers. So that Arabic can be said to be far written in Indonesian but close verbally in the everyday religious life of students.This study describes vocabulary learning by singing in the process of learning Arabic for children. The research subjects of class 1 MIN 1 Malang city in the academic year 2018/2019, using a type of qualitative research with the method of collecting observation and interview data. The results of this study indicate that singing in vocabulary / mufrodat teaching can increase students' motivation and learning attractiveness towards Arabic so that students can be happy to add new Mufrodat next to be helped to write because they feel close to the word taught by singing. Arabic is close verbally but far in reading and writing for children can be overcome by using songs and songs as an alternative to teaching Arabic for children.Â